«Високе» і «низьке» у творчості народній і писемній - Бошкович-Стуллі, М. (Народна творчість та етнологія, 2011)
«The high» and «the low», – these categories can be examined and as mythical, as poetic image of space, as metaphorical recreation of human fate, as a public vertical line of human possibilities, as the valued step at the analysis of artistic styles and at the same time as violation of such evaluation. All these aspects adds to the theme as as an object of attention in the article; the relations of «high» and «low» culture, culture folk comes forward and «lordly» in the past centuries. Categories highly/low, higher/below are examined in various scientific studios – mythological, culturological, sociological, from the point of view of theory of literature, in historical and literary measuring. Visoko i nisko, gore i dolje može se promatrati kao mitološko značenje, kao poetska vizija prostora, kao metafora ljudske sudbine, kao društvena vertikala moći, kao vrijednosna ljestvica književnih stilova, kao narušavanje takvoga vrednovanja. Sve su to tek dopune temi kojom se želimo baviti. Zanimljivi su za nas odnosi visoke i niske kulture (prvenstveno verbalne, književne), kulture pučke i gospodske u proteklim stoljećima. Pojmovi se visoko/nisko, gore/dolj